Impact of Right-Sided Nephrectomy on Long-Term Outcomes in Retroperitoneoscopic Live Donor Nephrectomy at Single Center - Kazuya Omoto; Taiji Nozaki; Masashi Inui; Tomokazu Shimizu; Toshihito Hirai; Yugo Sawada; Hideki Ishida; Kazunari Tanabe (Journal of Transplantation)
Objective. To assess the long-term graft survival of right-sided retroperitoneoscopic live donor nephrectomy (RPLDN), we compared the outcomes of right- and left-sided RPLDN. Methods. Five hundred and thirty-three patients underwent live donor renal transplantation with allografts procured by RPLDN from July 2001 to August 2010 at our institute. Of these, 24 (4.5%) cases were selected for right-sided RPLDN (R-RPLDN) according to our criteria for donor kidney selection. Study variables included peri- and postoperative clinical data. Results. No significant differences were found in the recipients' postoperative graft function and incidence of slow graft function. Despite significant increased warm ischemic time (WIT: mean 5.9 min versus 4.7 min, ) in R-RPLDN compared to that in L-RPLDN, there was no significant difference between the two groups regarding long-term patient and graft survival. The complication rate in R-RPLDN was not significantly different compared to that in L-RPLDN (17% versus 6.5%, ). No renal vein thrombosis was experienced in either groups. Conclusions. Although our study was retrospective and there was only a small number of R-RPLDN patients, R-RPLDN could be an option for laparoscopic live donor nephrectomy because of similar results, with the sole exception of WIT, in L-RPLDN, and its excellent long-term graft outcomes.